An Analysis of Metaphors Translated in English Translations of the Holy Qur’ān Written by Women - Bokhari, Dr. Abida; Ramish, Muhammada; Aman ullah, Bi Bi Saima (Al-Amīr Research Journal for Islamic Studies, 2024)
This paper concerns the English translation of metaphors in the Holy Qur’ān. It is based on an analytical and comparative study of metaphor’s translation used in six English translations of the Holy Qur’ān written by women. Four verses with two metaphorical images from the Holy Qur’ān have been selected. The definition of metaphor, its different types, as well as the strategies for translating them, have been discussed. However, this research paper deals only with the classification of metaphors according to Dickin’s approach. Metaphors’ translation strategies adopted by women translators have been compared with each other. However, the analysis of these strategies is based on Newmark’s strategies to translate metaphors. Tables of adopted strategies and their frequencies have been provided. At the end of the paper, a conclusion along with some recommendations has been given. Keywords: Holy Qur’ān, metaphor, Newmark, translation strategies.